2014
DOI: 10.1002/jssc.201400517
|View full text |Cite
|
Sign up to set email alerts
|

Combination of a sub‐3 μm superficially porous particle packed column with charged aerosol detection for the simple and sensitive measurement of nine macrolides in human urine

Abstract: Due to the lack of chromophores in many macrolides, analytical methods based on mass spectrometry and electrochemical detection coupled to liquid chromatography have been suggested to be suitable for the quantification of macrolides in complex matrices. In this study, a simple and sensitive analytical method was established for the simultaneous measurement of nine macrolides in human urine by combining a sub-3 μm superficially porous particle packed column with charged aerosol detection. After thorough investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The analytical methods reported previously for the quantification of CLA in biological fluids as well as in formulations include microbiological bioassay [5] and chemical methods, such as ultraviolet (UV) spectrophotometry [6], spectrofluorimetry [7], thin layer chromatography [8], voltammetry [9,10], and capillary zone electrophoresis [11,12]. A survey of literature revealed that most techniques used for the determination of this drug are highperformance liquid chromatography with electrochemical detection [13][14][15][16][17], mass spectrometry [18][19][20][21], fluorescence detection after pre-column derivatization [22], UV detection [23][24][25], and diode array detection [26]. These methods were time-consuming, tedious, and mainly devoted to the determination of CLA in biological fluids.…”
Section: Introductionmentioning
confidence: 99%
“…The analytical methods reported previously for the quantification of CLA in biological fluids as well as in formulations include microbiological bioassay [5] and chemical methods, such as ultraviolet (UV) spectrophotometry [6], spectrofluorimetry [7], thin layer chromatography [8], voltammetry [9,10], and capillary zone electrophoresis [11,12]. A survey of literature revealed that most techniques used for the determination of this drug are highperformance liquid chromatography with electrochemical detection [13][14][15][16][17], mass spectrometry [18][19][20][21], fluorescence detection after pre-column derivatization [22], UV detection [23][24][25], and diode array detection [26]. These methods were time-consuming, tedious, and mainly devoted to the determination of CLA in biological fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Charged aerosol detector (CAD) is a relatively new type of HPLC detector introduced by Dixon and Peterson and represents an alternative detection method for non‐volatile analytes that lack chromophore groups, such as topiramate . CAD has been described as advantageous over other universal detectors due to its high sensitivity, consistent response, and broad dynamic range . In a system employing a CAD, the HPLC eluent is nebulized by nitrogen carrier gas that transforms the liquid phase into small droplets.…”
Section: Introductionmentioning
confidence: 99%